Legislative linked open data: A proposal of linked open data modelling for legislative information - Brandt, Mariana Baptista [UNESP]; Borsetti Gregorio Vidotti, Silvana Aparecida [UNESP]; Santarem Segundo, José Eduardo [UNESP] (My University, 2018)
This research aimed to create a linked open data (LOD) model using RDF (Resource Description Framework) for a legislative dataset from the House of Representatives. It has proceeded a literature review embracing the concepts of open data, open government data, linked data and linked open data followed by an applied research for a data modelling of legislative data in linked open data using RDF. The dataset “Deputies” was selected for this research. It covers information about political parties, state, e-mail, legislature among others, about the congressmen. It was observed that modelling the dataset using RDF is possible by reusing vocabularies and frameworks already established in Semantic Web e.g. Dublin Core, Friend of a Friend (FOAF), RDF and RDF Schema, together with correlated vocabularies like the Italian House of Representatives and the French National Assembly ontologies. As recommended by Linked Data best practices, the resources were also related to other LOD such as Geonames and DBpedia for semantic enhancement. The study allows us to conclude that making government data available, especially legislative data can be done according to the recommendations and best practices from W3C (World Wide Web Consortium). This practice integrates legislative data on the Web of Data and increase the possibilities of data reuse in transparency and oversight projects, which approaches citizens to the Congress and to their representatives.
Modelo de dados abertos conectados para informaÇÃo legislativa
Keywords: Legislative Data; Linked Data; Linked Open Data; Open Government; Semantic Web